Paulo Freire Rousseau of the twentieth century - Bhattacharya, Asoke; SpringerLink (Online Service). (Rotterdam SensePublishers, 2011)
A wealth of literature has been published about Paulo Freire, but nothing as comprehensive as this book. This book distinguishes itself by a detailed account of the historical, economic and social context , and on this basis Professor Bhattacharya draws a fascinating and comprehensive picture of one of the most famous and influential educational philosophers from the last half of the twentieth century? says Professor Ove Korsgaard of Danish University School of Education, Denmark and a doyen of adult education in Scandinavia. Besides, it provides a chapterwise critique of all the major works of Paulo Freire. This volume should prove to be extremely useful to students, teachers and researchers.
Electronic reproduction.
Keywords: Freire, Paulo, 1921-1997 -- Criticism and interpretation; Education -- Philosophy; Electronic books